The effects of handball and waterpolo training on blood nitric oxide and oxidative stress levels - Montazeri, Nadia; Turgay, Faruk; Denerel, Nevzad (My University, 2023)
Objective: Nitric oxide (NO) is a gas that has vasodilatory, antioxidant and metabolic regulatory properties. Both NO and oxidative stress (OS) are risk factors for atherosclerosis (AS). These properties of NO, therefore play a critical role in training adaptations. Handball and water polo are team sports requiring aerobic and anaerobic energy. However, since they are practised in different environments, their effects on blood NO and OS levels may be different. Therefore, this study aimed to compare the effects of these two team sports on blood NO and OS levels. Material and Methods: Male handball players (HG, n=14), water polo players (WPG, n=12) and a control group (CG, n=13) of sedentary players participated in this study. Physical and physiological measurements, including critical velocity of the participants were made. The participants' fasting serum NO and OS indicators, and total antioxidant/oxidant status (TAS/TOS) were determined. Results: TAS levels of HG and WPG were significantly lower than those of the control group (p<0.05, p<0.01), whereas their NO levels were higher than those of CG (19.5% and 25.7% respectively, p>0.05). No significant difference was present for NO between HG and WPG. A significant negative correlation was present between CV and serum NO level, and there was a positive correlation between maximal 1500 m running time and NO for handball players. Conclusons: The findings of the study reveal that although training caused a significant decrease in antioxidant capacity in two team sports athletes, serum NO levels improved, thereby contributing to cardiovascular health. NO may harm aerobic endurance performance, but it had a beneficial effect on anaerobic power in the handball group, and none for water polo players.
Keywords: Nitric oxide; oxidative stress; water polo; Handball; critical velocitiy